2009
DOI: 10.1093/sleep/32.3.351
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of 6-Month Nightly Ramelteon Administration in Adults with Chronic Primary Insomnia

Abstract: In adults with chronic insomnia, long-term ramelteon treatment consistently reduced sleep onset, with no next-morning residual effects or rebound insomnia or withdrawal symptoms upon discontinuation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
114
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(117 citation statements)
references
References 43 publications
1
114
0
2
Order By: Relevance
“…This indication is supported by self-report and polysomnographic studies showing that sleep onset is hastened along in a dosage range of 4 to 32 mg [59][60][61][62][63][64], although the indicated clinical dose is 8 mg. The incidence or insomnia increases in the elderly, and studies of remelteon have been conducted in elderly primary insomniacs, which show its efficacy in this population [60,61].…”
Section: Efficacymentioning
confidence: 95%
See 1 more Smart Citation
“…This indication is supported by self-report and polysomnographic studies showing that sleep onset is hastened along in a dosage range of 4 to 32 mg [59][60][61][62][63][64], although the indicated clinical dose is 8 mg. The incidence or insomnia increases in the elderly, and studies of remelteon have been conducted in elderly primary insomniacs, which show its efficacy in this population [60,61].…”
Section: Efficacymentioning
confidence: 95%
“…The incidence or insomnia increases in the elderly, and studies of remelteon have been conducted in elderly primary insomniacs, which show its efficacy in this population [60,61]. Tolerance to sleep onset-inducing effects did not develop in the 6-to 12-month studies that have been conducted [63,64]. Interestingly, unlike the BzRAs, polysomnographic measures of efficacy show a more robust effect than patient reports.…”
Section: Efficacymentioning
confidence: 99%
“…O mesmo estudo não identificou potencial para indução de insônia de rebote, sintomas de abstinência, potencial para abuso e/ou dependência, comprometimento cognitivo ou motor, sugerindo ser uma opção terapêutica em pacientes com história prévia de abuso de substâncias e em pacientes idosos 22 .…”
Section: Melatoninérgicos 1) Ramelteonunclassified
“…Some studies have reported that administration of sleeping pills 30 min before bedtime shortens sleep latency and increases total sleep time. [1][2][3] Numerous studies have defined normal sleep onset latency as less than 30 min, [4][5][6] and clinical practice guidelines for insomnia also state that 30 min is an optimal length of time for sleep latency. 7 In one study, a sleep latency of 31 min was found to be the most defensible quantitative criteria for insomnia.…”
Section: Introductionmentioning
confidence: 99%